Chemo‐port insertion: A cause of vocal cord palsy. (24th June 2015) - Alazzawi, Sarmad; Hindi, Khalid; Malik, Ausama; Wee, Chong Aun; Prepageran, Narayanan
<x xml:space="preserve">Abstract</x> We describe extremely rare cases of vocal cord palsy following surgical insertion of a chemo port. Our cohort consisted of patients with cancer who developed hoarseness immediately after central venous line placement for the administration of chemotherapy, with vocal cord palsy confirmed with flexible laryngoscopy. Given the timing, central venous line placement appears to be the most likely cause. Laryngoscope, 125:2551–2552, 2015